Antibacterial, in vitro antitumor activity and structural studies of rhodium and iridium complexes featuring the two positional isomers of pyridine carbaldehyde picolinic hydrazone ligand - Narasinga Rao Palepu (Arabian Journal of Chemistry, 2018)
Half-sandwich organometallic rhodium and iridium complexes [1–6] have been synthesized with ligands L1 (L1 = Pyridin-2-ylmethylene picolinichydrazine) and L2 (L2 = Pyridin-3-ylmethylene picolinichydrazine). Treatment of [{Cp∗MCl2}2] (M = Rh/Ir) with L1 in methanol has yielded mononuclear cationic complexes such as [{Cp∗M(L1N∩N)Cl}]PF6 where {M = Rh (1) and Ir (2)} and dinuclear complexes such as [{(Cp∗MCl)2(L1N∩N, N∩N)}]PF6 where {M = Rh (3) and Ir (4)} in 1:2 and 1:1 metal dimer to ligand ratios respectively. Reactions of [{Cp∗MCl2}2] with L2 in both 1:2 and 1:1 metal dimer to ligand ratios have yielded two metalla-macrocyclic dinuclear and dicationic complexes such as [{Cp∗M(L2N∩NμN)}2](PF6)2 where {M = Rh (5) and Ir (6)}. Spectroscopic and crystallographic data were used to elucidate the structures of the synthesized complexes. The in vitro antitumor evaluation of the complexes 1 and 2 by fluorescence based apoptosis study revealed their antitumor activity against Dalton’s ascites lymphoma (DL) cells. The antibacterial evaluation of complexes 1, 2, 5 and 6 by agar well-diffusion method revealed their significant activity against the two species considered viz., Proteus vulgaris (MTCC 426) and Vibrio parahaemolyticus (MTCC 451) with zone of inhibition up to 43 mm. The docking study with few key enzymes associated with cancer viz., ribonucleotide reductase, thymidylate synthase, thymidylate phosphorylase and topoisomerase II revealed their strong interactions with complexes under study. Complexes 1–6 exhibited a HOMO (highest occupied molecular orbital) – LUMO (lowest unoccupied molecular orbital) energy gap from 2.95 eV to 3.59 eV. TDDFT calculations explain the nature of electronic transitions and found well agreement with the experiments. Keywords: Rhodium dimer, Pyridin-2-ylmethylene picolinichydrazine, Metalla-macrocycles, Antitumor, Antibacterial, TDDFT